THE STRUCTURE AND HYDROLOGY OF THE EARLY DYNASTIC CITY OF LAGASH (TELL AL-HIBA) FROM SATELLITE AND AERIAL IMAGES. (December 2022) - Hammer, Emily; Stone, Elizabeth; McMahon, Augusta
Abstract : Satellite imagery and UAV (drone) photos taken at Lagash (modern Tell al-Hiba) after rainstorms and at times of elevated soil moisture show dense near-surface architecture that dates mostly to the Early Dynastic III period (c. 2600–2350 BCE) and covers several hundred hectares. Archaeological knowledge of Mesopotamian urban structure has mostly been limited to isolated excavated neighbourhoods, such as at third millennium BCE Tutub (Khafajah) or Eshnunna (Tell Asmar), and early second millennium BCE Ur (Tell al-Muqayyar). The morphology of Tell al-Hiba and the quality of the imagery sets create a unique situation that enables the reconstruction and comparison of neighbourhoods across almost the whole of the city of Lagash. Mapping of near-surface architectural remains, streets, and water features reveals a discontinuous city located within a watery, possibly marshy environment.